Necesidad de garantizar el ejercicio efectivo de la acción de habeas corpus.- reforma al artículo 45 de la ley de garantías jurisdiccionales y control constitucional - Jaramillo Mena, Jorge Humberto (2016)
The matrix problem generated after the process of analysis and deduction prior recognition of the techniques and procedures of a legal investigation of applied character, focuses on the review and theoretical study of important institutions and legal figures of relevant connotation in the area of positive law; Consequently my subject area i located in the review of some aspects related to the procedural constitutional law, that being part of public law and of relevance and significance within the human relations, constitutes an ideal space to identify legal problems that affect and general negative impacts on the Community. Against the background described in the paragraph above, I should like to refer to the action of habeas corpus, because as well as the other jurisdictional guarantees provided for in the law on the matter in the constitutional jurisdiction, you can also access the protection of rights through this action; for this review briefly what is stated in article 43 of the Law on judicial guarantees and constitutional control, the same that verbatim relates: "Art. 43.- Object.- The action of habeas corpus is intended to protect the freedom, life, physical integrity and other related rights of the person deprived or restricted of freedom, by public authority or by any person(..)" The provision that above we understand which is the subject of the guarantee of habeas corpus and its scope of protection, however the contradiction occurs when in article 45 of the same body of law in relation to the rules of application, refers that: "Judges and judges shall observe the following rules: (…) 1. In the event of the occurrence of any form of torture there will be the release of the victim, their comprehensive care and specialized, and the imposition of alternative measures to deprivation of liberty. The problem identified precisely is evidenced by the contradiction between the art. 45 of the law in question and the art. 89 of the Constitution which says that in the event of verified any form of torture, inhuman, cruel or degrading treatment shall be the release of the victim, their comprehensive care and specialized, and the imposition of alternative measures to deprivation of liberty when applicable".